Assimilation Process In Tamil And Arabic Languages: A Contrastive Study - Mohammed Cassim Sithy Shathifa; Mohammed Haneefa Abdul Munas; Mohamed Haniffa Mohamed Nairoos; Muhammadu Sainulabdeen Zunoomy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Whenever a person learns a second or foreign language, who is aware of the grammar of his mother tongue alone, it significantly impacts learning the second language. Challenges faced in learning a second or foreign language can be decreased by the comparative study of the grammar of the two languages. Accordingly, this research tries to study sound assimilation in Arabic and Tamil languages comparatively. The research problem concerns whether there are similarities between the two different languages from two other families in the assimilation process. This research aims at a comparative study of the assimilation of sound between Arabic and Tamil languages. This object is tried to be achieved through the qualitative research methodology under descriptive analysis for the secondary data analysis. While both languages are available from two different families, the assimilation process happens in consonant letters alone. Assimilation occurs in both of these languages due to the factors like place of articulation, characteristics of sounds, and place of vowel and consonant letters. In contrast, in the Tamil language, a word is divided into morphemes, and the homogeneity between the morphemes impacts the assimilation of sound. However, dissimilation occurs in these two languages due to sounds' characteristics and vowels' impact on consonants. The morphemes of the Tamil language have unique meanings. This research has identified that the types of good assimilation are the same for the two languages, while complete assimilation is an added type in Arabic. On such a background, this research would hopefully assist those who learn Arabic as a second language with the mother tongue of Tamil.